Direct TLC Optical Resolution of Two Sulphur-Containing DL-a-Amino Acids Using Vancomycin as Chiral Selector - Lian, Xiao; Chen, Xue-Xian; Zi, Min; Yuan, Li-Ming (Asian Journal of Chemistry, 2015)
Direct TLC enantioseparation for naturally occurring two sulphur-containing a-amino acids, cysteine and methionine, were achieved on silica gel plates using vancomycin as chiral impregnating reagent with only one developing solvent n-butanol-methanol-water- acetic acid (5:1.6:1.2:0.4, v/v/v/v). The effects of developing solvents, the ratio of mobile phase, concentration of chiral selector and temperature on the enantioseparation had been studied. This is the first report on TLC direct resolution of cysteine and methionine using vancomycin as chiral selector with same developing solvent.